Climate change concern and the desire to travel: How do I justify my flights?. (July 2021) - Árnadóttir, Áróra; Czepkiewicz, Michał; Heinonen, Jukka
Highlights: The highly climate aware were not willing to quit flying and few were open to change. Justifications to continue flying differed depending on climate awareness level. Emphasis was placed on the benefits of travel, potentially due to harsh local weather. A lack of alternative transport modes contributed to the vast attitude behaviour gap. Abstract: There is an urgent need to reduce emissions from the aviation sector. Although awareness of climate change is growing, few are willing to alter their flight behaviour. Through a qualitative analysis of interview materials collected from Reykjavik Capital Region residents, this study explores how globally affluent, highly mobile young urbanites justify their international travel by plane, despite their climate change awareness, and if they are willing to change their behaviour. Six themes of justifications to continue air travel were identified; shifting responsibility, compensatory behaviours, lack of knowledge or awareness, lack of other options, benefits outweighing impacts, and carbon offsetting. Their use differed depending on respondents' level of climate change awareness and willingness to reduce air travel, but willingness to reduce travel did not differ between awareness level scores. None were willing to quit flying regardless of their level of awareness. Compared with previous literature, we found a greater emphasis placed on the benefits of air travel. We suggest policy uptake for both individual and collective realms, such as kerosene tax and mandatory carbon offsetting, as shifting responsibility can delay action regardless of the way in which it is shifted, and reductions in these realms can only happen in concert. Other sources of well-being should be emphasized and the social norm around frequent travel actively challenged. Knowledge on the specific climate impacts of flights should be better communicated to the public and put into perspective with the global fair share of emissions and steep mitigation curves to keep warming below 1.5°.